2020
DOI: 10.1152/ajpgi.00161.2019
|View full text |Cite
|
Sign up to set email alerts
|

A story of liver and gut microbes: how does the intestinal flora affect liver disease? A review of the literature

Abstract: Each individual is endowed with a unique gut microbiota (GM) footprint that mediates numerous host-related physiological functions, such as nutrient metabolism, maintenance of the structural integrity of the gut mucosal barrier, immunomodulation, and protection against microbial pathogens. Because of increased scientific interest in the GM, its central role in the pathophysiology of many intestinal and extraintestinal conditions has been recognized. Given the close relationship between the gastrointestinal tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 213 publications
1
82
0
Order By: Relevance
“…Obesity is directly related to the development of non-alcoholic fatty liver disease (NAFLD) [ 2 ]. NAFLD is characterized by a disease spectrum ranging from simple hepatic steatosis (i.e., non-alcoholic fatty liver, NAFL) to non-alcoholic steatohepatitis (NASH) in as many as 40% of patients [ 3 , 4 , 5 ]. Over time, NASH can further promote liver injury, causing fibrosis and, potentially, cirrhosis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is directly related to the development of non-alcoholic fatty liver disease (NAFLD) [ 2 ]. NAFLD is characterized by a disease spectrum ranging from simple hepatic steatosis (i.e., non-alcoholic fatty liver, NAFL) to non-alcoholic steatohepatitis (NASH) in as many as 40% of patients [ 3 , 4 , 5 ]. Over time, NASH can further promote liver injury, causing fibrosis and, potentially, cirrhosis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiota is a huge and complex system that is influenced by numerous factors, and is associated with host immunity. It has been reported that gut microbiota and host immunity are associated via diet, intestinal absorption and enterohepatic circulation ( 77 , 78 ). Therefore, it may be a promising research direction to determine the association between gut microbiota and immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the microorganisms that arrive in the liver are eliminated due to the balance between tolerance and inflammation of the hepatic microenvironment [ 3 , 20 , 21 ]. Brucella has a panoply of defensive strategies to evade immune response, including intracellular lifestyle and the prevention of the development of an appropriate adaptive immune response [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%